Annotated record and spectrochemical analyses of Mn nodules from Georgia Strait, British Columbia obtained during CNAV Laymore in 1970 - Christopher Howard Pharo (PANGAEA, 1972)
A study of the distribution, dispersal and composition of surficial sediments in the Strait of Georgia, B.C., has resulted in the understanding of basic sedimentologic conditions within this area. The Strait of Georgia is: a long, narrow, semi-enclosed basin with a restricted circulation and a single, main, sediment source. The Fraser. River supplies practically all the sediment now being deposited in the Strait of Georgia, the bulk of it during the spring and summer freshet. This river is building a delta into the Strait from the east side near the south end. Ridges of Pleistocene deposits within the Strait and Pleistocene material around the margins, like bedrock exposures, provide local sources of sediment of only minor importance. Rivers and streams other than the Fraser contribute insignificant quantities of sediment to the Strait. Sandy sediments are concentrated in the vicinity of the delta, and in the area to the south and southeast. Mean grain size decreases from the delta toward the northwest along the axis of the Strait, and basinwards from the margins. Silts and clays are deposited in deep water west and north of the delta front, and in deep basins northwest of the delta. Poorly sorted sediments containing a gravel component are located near tidal passes, on the Vancouver Island shelf area, on ridge tops within the Strait, and with sandy sediments at the southeastern end of the study area. The Pleistocene ridges are areas of non-deposition, having at most a thin veneer of modern mud on their crests and upper flanks. The southeastern end of the study area contains a thick wedge of shandy sediment which appears to be part of an earlier delta of the Fraser River. Evidence suggests that it is now a site of active submarine erosion. Sediments throughout the Strait are compositionally extremely similar, with-Pleistocene deposits of the Fraser River drainage basin providing the principal, heterogeneous source. Gravels and coarse sands are composed primarily of lithic fragments, dominantly of dioritic to granodloritlc composition. Sand fractions exhibit increasing simplicity of mineralogy with decreasing grain-size. Quartz, felspar, amphibole and fine-grained lithic fragments are the dominant constituents of the finer sand grades. Coarse and medium silt fractions have compositions similar to the fine sands. Fine silts show an increase in abundance of phyllosilicate material, a feature even more evident in the clay-size fractions on Montmorillonite, illite, chlorite, quartz and feldspar are the main minerals in the coarse clay fraction, with minor mixed-layer clays and kaolinite. The fine clay fraction is dominated by montmorillonite, with lesser amounts of illite and chlorite. The sediments have high base-exchange capacities, related to a considerable content of montmorillonite. Magnesium is present in exchange positions in greater quantity in Georgia Strait sediments than in sediments from the Fraser River, indicating a preferential uptake of this element in the marine environment. Manganese nodules collected from two localities in the Strait imply slow sediment accumulation rates at these sites. Sedimentation rates on and close to the delta, and in the deep basins to the northwest, are high.
Supplement to: Pharo, CH (1972): Sediments of the Central and Southern Strait of Georgia, British Columbia [dissertation]. University of British Columbia, Vancouver, Canada, 290 pp, https://open.library.ubc.ca/cIRcle/collections/831/items/1.0052573